(untitled) (Journal of Health Sciences, 2025)
Anomalous left coronary artery from the pulmonary artery (ALCAPA) is a rare heart defect present at birth. In this condition, the left coronary artery, which normally comes from the aorta, instead starts from the pulmonary artery. This abnormal connection can lead to reduced blood flow to the heart muscle, causing damage like heart attacks and increasing the risk of serious heart rhythm problems or sudden cardiac arrest (SCA). Diagnosis is made through imaging studies, and treatment often involves surgical correction to restore normal coronary circulation. The prognosis of ALCAPA largely depends on the age at which it is diagnosed and the timing of treatment. Early intervention is crucial for improving outcomes. This case report presents a 11-year-old girl, who is an athlete, with late presentation of ALCAPA syndrome in the form of ventricular fibrillation leading to SCA. She had no previous symptoms, the electrocardiogram showed no abnormalities except for left axis deviation and the several echocardiograms showed no enlargement of the left ventricle, with possible big right coronary artery. ALCAPA has been confirmed by computed tomography coronary angiographyscan. Child was surgically treated by coronary artery transfer for ALCAPA with satisfactory outcome. The implantation of an implantable cardioverter defibrillator is still under consideration.